1999
DOI: 10.1089/jwh.1.1999.8.623
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Low-Fat Diet on Incidence and Severity of Migraine Headaches

Abstract: Migraine headaches are a common, debilitating syndrome causing untold suffering and loss of productivity. A review of the literature indicates that high levels of blood lipids and high levels of free fatty acids are among the important factors involved in triggering migraine headaches. Under these conditions, platelet aggregability, which is associated with decreased serotonin and heightened prostaglandin levels, is increased. This leads to vasodilation, the immediate precursor of migraine headache. A high-fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 27 publications
(1 reference statement)
4
67
0
5
Order By: Relevance
“…Studies indicated that a low-fat diet was associated with significant decreases in headache frequency, intensity, duration, and medication intake. 5 The presence of elevated CRP with MA, MoA, and transformed migraine in this study further supports the role of inflammation in migraine. 11,19,20 As none of the Abbreviations: MA, migraine with aura; MoA, migraine without aura, BMI, body mass index; SBP, systolic blood pressure; DBP, diastolic blood pressure; CRP, C-reactive protein; TC, total cholestrol; TG, triglycerides; CCA-IMT, common carotid artery intimamedia thickness; FMD%, brachial artery flow-mediated dilatation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Studies indicated that a low-fat diet was associated with significant decreases in headache frequency, intensity, duration, and medication intake. 5 The presence of elevated CRP with MA, MoA, and transformed migraine in this study further supports the role of inflammation in migraine. 11,19,20 As none of the Abbreviations: MA, migraine with aura; MoA, migraine without aura, BMI, body mass index; SBP, systolic blood pressure; DBP, diastolic blood pressure; CRP, C-reactive protein; TC, total cholestrol; TG, triglycerides; CCA-IMT, common carotid artery intimamedia thickness; FMD%, brachial artery flow-mediated dilatation.…”
Section: Discussionsupporting
confidence: 76%
“…Migraine is a disease with a presumed vascular mechanism. 3 Recently, several epidemiologic, longitudinal, case-control, and cohort studies demonstrated association between migraine and vascular risk comorbid medical conditions including: increased body mass index (BMI) or obesity, 4 hypercholesterolemia/dyslipidemia, 5 hypertension, 6 impaired insulin sensitivity, 7 ischemic stroke in young adults, 8 and coronary heart disease. 9 These associations or comorbidities are not explained by bias.…”
mentioning
confidence: 99%
“…Finally, it has been reported that diet with low-fat intake could reduce the headache frequency and intensity [33].…”
Section: Fasting Glucose Metabolism and Migrainementioning
confidence: 98%
“…First, in a small trial including only seven patients with no control group, a carbohydrate-rich diet, low in protein-tryptophan, was shown to favourably affect headache, and the efficacy of the dietary intervention was related to a reduced intake of migraine-precipitating foods with a concomitant increase in the brain serotonin levels [11]. Thereafter, the lipid components of the diet were investigated: it has been suggested that a lipid-rich diet might be responsible for headache because the plasma serotonin levels are reduced in relation to the increased platelet aggregation [12], whilst a very low-lipid diet (about 20 g daily) might help in preventing headache [13]. More recently, the use of a ketogenic diet has been proven to reduce the frequency of migraine attacks [14,15].…”
Section: Introductionmentioning
confidence: 99%